(3GdbGfhf GdeSYhOis - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI hLOGhd GdebGdGJ GdEMOi YTQ GdYGde HcdjJg LSe eSJOjQ GdTcd s
(3BNQgG (B:s
(3bHd GdGfJgGA hEPG HdZJ gPG GdehVY ef GdcJGH , abO Cf GNJJGeg HGdMeO ddg GdhGMO GdYOd Pi Gdef hGdWhd s
(3ajgG QShe hLOGhds
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B241s
Keywords: (3Gdadcs